Assessment Of Cervıcal Vertebral Dımensıons In Skeletal Maturatıon - Sönmez Fıratlı; Evren Öztaş (Galenos Yayinevi, 1996)
The aim of this study is to evaluate cervical vertebral dimensional changes due to the growth and to determine whether these changes could be used as a predictor of skeletal maturation. Cross sectional data included lateral cephalometric radiographs taken before ortodontic treatment of 325 patients with different kinds of malocclusions (182 girls-143 boys) aged from 9 to 15 years. Care was taken in the selection of the subjects which have skeletal and chronological age in accordance. Seventeen reference points were recorded on the lateral cephalometric radiographs related to the first, second, third, and fourth cervical vertebrae, and thirteen measurements were performed. Nine ratios were calculated to evaluate the relationship between the chronological age and the changes in the size of the cervical vertebrae. ANOVA was performed to determine the differences between the chronological age groups. When a significance difference was found, Duncan's Multiple Range Test was performed to determine which of the means were significantly different. The level of significance for all tests were at 0.05. Significant differences were found between the chronological age and the first, second, third, fifth, eight, and ninth mean ratios. The first, second, third, and ninth mean ratios differed significantly with some of the age groups while the fifth and the eight mean ratios varied significantly with most age groups. Mean ratio of the anterior body height to lower body width increased significantly due to the acceleration of the growth and the increase in age with values of 0.53 to 0.81 and 0.51 to 0.86 respectively for the third and fourth cervical vertebrae. Ratios of the cervical vertebral dimensions are proportional to the increase in age and acceleration of the growth. Ratios of the anterior body height to lower body width of the third and the fourth cervical vertebrae would be used to predict and determine the sekelal age.